2018
DOI: 10.1590/s0100-83582018360100124
|View full text |Cite
|
Sign up to set email alerts
|

Management of Charcoal Rot of Mungbean by Two Trichoderma Species and Dry Biomass of Coronopus didymus

Abstract: A pot experiment was carried out to check the effect of Coronopus didymus (L.) Sm. dry biomass application (1%, 2% and 3% w/w) and two species of Trichoderma (T. viride and T. aureoviride) on growth and physiology of mungbean [Vigna radiata (L.) WIlczek] under biotic stress of Macrophomina phaseolina (Tassi) Goid. Inoculation of M. phaseolina (positive control) reduced plant survival, shoot and root length as well as plant dry biomass by 22%, 52%, 61% and 64%, respectively, over the negative control (without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Application of dry biomass of C. album, T. harzianum, and T. viride not only enhanced the growth of tomato plants but also protected them from disease by stimulating resistance through inducing greater photosynthetic pigment, phenolics, and activities of enzymes probably to appropriate level to get rid of pathogen pressure (Awan et al 2018). Similar results have been obtained previously due to effect of soil amendment or biocontrol agents in Vigna mungo and V. radiata against charcoal rot caused by Macrophomina phaseolina (Javaid et al 2018; Shoaib et al 2018) and in chickpea against collar rot incited by S. rolfsii (Shoaib et al 2019). Fungicidal action of dry biomass of C. album or Trichoderma spp.…”
Section: Effect Of Soil Amendments On Plant Physiologysupporting
confidence: 85%
“…Application of dry biomass of C. album, T. harzianum, and T. viride not only enhanced the growth of tomato plants but also protected them from disease by stimulating resistance through inducing greater photosynthetic pigment, phenolics, and activities of enzymes probably to appropriate level to get rid of pathogen pressure (Awan et al 2018). Similar results have been obtained previously due to effect of soil amendment or biocontrol agents in Vigna mungo and V. radiata against charcoal rot caused by Macrophomina phaseolina (Javaid et al 2018; Shoaib et al 2018) and in chickpea against collar rot incited by S. rolfsii (Shoaib et al 2019). Fungicidal action of dry biomass of C. album or Trichoderma spp.…”
Section: Effect Of Soil Amendments On Plant Physiologysupporting
confidence: 85%
“…Many recent studies have shown that crude plant extracts as well as purified compounds isolated from various plant species are very effective in the control of fungal plant pathogens 3 – 5 . Studies have shown that plant extracts of Chenopodium spp., Senna occidentalis and Cirsium arvense can control growth of M. phaseolina and charcoal rot of mungbean 6 10 . From Azadirachta and Mango leaves, three flavonoids (–)-epi-catechin, (−)-epicatechin-3- O -β-glucopyranoside and 6-(phydroxybenzyl)taxifolin-7- O -β- d -glucoside were isolated and found effective against M. phaseolina 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Various reports show the widespread application of Trichoderma spp. such as T. asperellum, T. atroviride, T. gamsii, T. hamatum, T. harzianum, T. polysporum, T. virens and T. koningii as bio control agents effective against various soil-borne pathogens such as Phytophthora, Pythium, Aspergillus, Fusarium and Rhizoctonia [ (Moosa et al, 2017;Javaid et al, 2018;Sharma and Prasad 2018;Ingale and Patale (2019)] and organic amendments to suppress soil borne pathogens (Bonanomi et al, 2018). Several studies also suggest that when the bacterial or fungal antagonists such as P. flourescens or Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%